Morpholino Oligomer-Induced Dystrophin Isoforms to Map the Functional Domains in the Dystrophin Protein - Dunhui Li; Abbie M. Adams; Russell D. Johnsen; Susan Fletcher; Steve D. Wilton (Elsevier, 2020)
Dystrophin plays a crucial role in maintaining sarcolemma stability during muscle contractions, and mutations that prevent the expression of a functional protein cause Duchenne muscular dystrophy (DMD). Antisense oligonucleotide-mediated manipulation of pre-messenger RNA splicing to bypass Duchenne-causing mutations and restore functional dystrophin expression has entered the clinic for the most common DMD mutations. The rationale of "exon skipping" is based upon genotype-phenotype correlations observed in Becker muscular dystrophy, a milder allelic disorder generally characterized by in-frame deletions and internally truncated but semi-functional dystrophin isoforms. However, there is a lack of genotype-phenotype correlations downstream of DMD exon 55, as deletions in this region are rare and most single exon deletions would disrupt the reading frame. Consequently, the amenability of mutations in this region of the DMD gene to exon skipping strategies remains unknown. Here, we induced "Becker muscular dystrophy-like" in-frame dystrophin isoforms in vivo by intraperitoneal injection of peptide-conjugated phosphorodiamidate morpholino oligomers targeting selected exons. The dystrophin isoform encoded by the transcript lacking exons 56+57 appears to be more functional than that encoded by the 58+59-deleted transcript, as determined by higher dystrophin expression, stabilized β-dystroglycan, and less severe dystrophic pathology, indicating some potential for the strategy to address Duchenne-causing mutations affecting these exons.